Digestibility, digestible and metabolizable energy of Sacha Inchi (Plukenetia volubilis L) pelleted and extruded in guinea pigs (Cavia porcellus) - Díaz Céspedes, M. (2021)
The aim of this study was to evaluate the digestibility of nutrients and digestible and metabolizable energy of precooked and processed (pelletized and extruded) of seed and meal of sacha inchi (Plukenetia volubilis L) in guinea pigs. In each trial, 15 male guinea pigs, 3 months old and average weight of 700 g, were used. Pelletizing was carried out at 87 °C and extrusion at 105 °C. The digestibility and metabolic tests were determined using the substitution method and total excreta collection (faeces and urine). The apparent digestibility values (%) for dry matter, crude protein, crude fibre and ethereal extract for the pelleted seed were 54.4, 79.6, 27.0, 76.1 and for extruded seed were 48.7, 83.5, 16.2 and 81.7 respectively; while for pelletized cake were 82.5, 81.2, 98.7 and 65.9 and for extruded cake were 76.7, 83.2, 92.8 and 62.4. The digestible energy in the pelletized and extruded seed were 3296 and 3681 kcal/kg of dry matter, and in the pelletized and extruded cake they were 4621 and 4161 kcal/kg of dry matter, respectively. The metabolizable energy in the pelletized and extruded seed was 2676 and 3243 kcal/kg of dry matter, and in the pelletized and extruded cake it was 4346 and 4137 kcal/kg of dry matter, respectively. The type of processing did not affect the energy values in the sacha inchi seed and cake.